Addressing Communication Challenges: Implementation of an Enhanced EHR System with Patient Portal at a Vancouver Hospital - Anutej Sarode; Anurag Johri; Ankit Shreshtha; Clement Vadakkan (International Journal of Management and Data Analytics)
The new era of information and communications technology can greatly help the healthcare community, including suppliers, patients, staff and the top-level Management to bridge the gap of communication that is very important in the healthcare process. The inherent nature of society's current ways of communication largely hinges upon technology and networking. It is therefore prudent to leverage technology and evolved tools to be able to deliver the highest standards of patient care and safety. This paper highlights some of the studies done to identify the communication gap that healthcare providers face by looking at a Vancouver hospital as a case study and how the implementation of an enhanced EHR system can alleviate the communication gap. The paper looks into using state-of-the-art industry 4.0 technologies to improve hospital procedures, workflow processes, compliance, and enhance patient services that will lead to reduced costs and streamline of the core functions. This will in return benefit all patients, healthcare providers, suppliers, and other stakeholders.